Assessing functional disability and general health situation in patients with ankylosing sponylitis by asas health index - Can, Meryem (Clinical & Exper Rheumatology, 2018)
[Abstract Not Available]
WOS: 000440741300193
Keywords: Disability; Ankylosing; Sponylitis